Performance of Biofloc with Different Carbon Sources on the Growth of Catfish (Pangasius sp.) - Christina Virginia Nince; Ade Yulita Hesti Lukas; Wesly Pasaribu (Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine differences in carbon sources on the growth of catfish (Pangasius sp). The research design used was a completely randomized design (CRD) with 3 treatments and 3 replications. The treatments used were tapioca flour, corn starch, and wheat flour with a dose of 2 g/l carbon source water, 0.01 ml/l probiotics, and 3 g/l salts. The research variables observed were the growth pattern of catfish (Pangasius sp), the number of floc volumes, and water quality. The results showed that the performance of bioflocs with different carbon sources resulted in different daily growth patterns of catfish in each treatment, where the highest daily growth pattern was in the 60th-day tapioca flour treatment reaching 1.96%/day, corn starch treatment 1.57 %/day, and wheat flour treatment 1.74%/day. The results of water quality measurements for each treatment were still in the optimal range for the life and growth of catfish. Ammonia reduction in tapioca flour treatment was 0.57 mg/l, corn starch treatment was 0.36 mg/l, while in wheat flour treatment there was no reduction in ammonia due to low temperature at the end of the study so it interfered with bacterial metabolism in assimilating nitrogen can still be tolerated by catfish (Pangasius sp).